The relationship between information technology and competitive advantages among small and medium tourism enterprises: Kota Kinabalu, Sabah / Leviana Andrew - Andrew, Leviana (2015)
Understanding how IT contributes to enterprises’ competitive advantages has long been of interest. While IT improved the business operation and communication to the extent that some enterprises managed to be competitive through the utilization of IT system, some enterprises seemed do not benefit from it. This study seeks to clarify the relationship between IT and competitive advantages among small and medium enterprises (SMEs) in Malaysia by focusing on tour and travel agents in Kota Kinabalu, Sabah. Several theories such as the resource-based view, market-based view and Porter’s model of competitiveness are discussed to further explain the association between these two variables. IT Infrastructure, IT Capability Agent and IT Competencies are the elements of IT while Customer Service, Low Cost, Agility, Innovation and Differentiation are the elements of competitive advantages that were included in this study. The element of strategic planning is added in the relationship as a moderator to the relationship between variables. A total of 111 responses from 364 distributed questionnaires were used for the analysis of this study. Factor analysis extracted one more factor in IT elements which is Modularity and deleted out the element of agility from competitive advantages. The results showed that the relationship between IT and competitive advantages is positive, high and significant; with element IT Infrastructure has the most influence on competitive advantages. However, the result of hierarchical regression analysis suggested that strategic planning does not moderate the relationship but it is more of a factor contributing to competitive advantages. These results showed the importance of integrating IT into business operation to meet information processing demands in dynamic environments. Further, this paper provides both theoretical and managerial implications for the industry and suggestions for future research.